OC-084 Colonic Motor Responses to a Meal and To Bisacodyl and Sensations Evaluated During High-Resolution Manometry (HRM) Differ Between Laxative-Refractory Slow Transit Constipation With or Without Pain. (17th August 2016) - Corsetti, M; Thys, A; Vanuytsel, T; Demedts, I; Deloose, E; Wolthuis, A; D'Hoore, A; Tack, J
Abstract : Introduction: In clinical practice colonic manometry is recommended to exclude colonic inertia (no response to meal and to drug stimulation, i.e. bisacodyl) in patients with slow transit laxative-refractory constipation (Bharucha 2013). As to date, this has not been assessed by colonic HRM in adults, our aim was to evaluate the sensations and colonic motor response to a meal and to bisacodyl in patients with slow-transit laxative-refractory constipation. Methods: Consecutive patients with slow-transit and laxative-refractory Rome III constipation were enrolled. During colonoscopy, an HRM catheter (40 sensors, 2.5 cm spaced) and an infusion tube were advanced as far as possible (caecum) and clipped to the mucosa. Colonic pressures were recorded for three hours before and two after a standardised meal, and for one hour after intra-colonic bisacodyl (10 mg). Abdominal discomfort, abdominal gas, desire to evacuate gas, desire to defecate and urgency to defecate were evaluated by means of 100 mm visual analogue scale (VAS) every 15 minutes. Number of pan-colonic pressurizations (PCPs, Corsetti 2015) and of low-amplitude (LAPSs, Dinning 2014) and high-amplitude propagating sequences (HAPSs, De Schryver 2002) were evaluated. A normal response to bisacodyl was identified by the occurrence of at least one HAPS. Data (mean±SD) were compared with those obtained in 10 healthy subjects (HS) (30±11 years, 5 females). Results: A total of 24 refractory slow-transit constipation patients (43±13 years, 22 females) were studied; 15 of these also referred pain or discomfort. As compared to HS, the total number of PCPs and of LAPSs was significantly lower in patients without pain (respectively, 19±21 vs 89±40 and 6±10 vs 52±39, all p < 0.01), while it did not differ in patients with pain (respectively, 60±41 and 38±46). PCPs significantly increased after a meal in HS and in patients with (p < 0.01) but not in those without pain (p = 0.20). Retrograde LAPSs increased significantly after the meal in HS (p = 0.01) but not in patients, regardless of the presence of pain (all p > 0.25). The response to bisacodyl was normal in all patients with pain and in 2/8 (25%) of those without pain (p = 0.01). VAS scores for discomfort differed significantly between patients with pain as compared to both patients without pain and healthy subjects (P = 0.006). Conclusion: Compared to slow transit patients without pain, patients with pain have a partially preserved response to meal (increased PCPs but not LAPSs), a higher prevalence of a normal response to bisacodyl and report higher score for discomfort during manometry. Disclosure of Interest: None Declared